The impact of trauma, substance abuse, and psychiatric illness on suicidal and self-harm behaviours in a cohort of migrant detainees: An observational, prospective study. (May 2022) - Marchi, Mattia; Artoni, Cecilia; Longo, Fedora; Magarini, Federica Maria; Aprile, Giovanni; Reggianini, Corinna; Florio, Debora; De Fazio, Giovanna Laura; Galeazzi, Gian Maria; Ferrari, Silvia
Background: According to the WHO, detainees attempt suicide ten times more than the general population. Aims: To investigate the impact of migration trauma on Suicidal and Self-Harm Behaviours (SSHB) of migrants in jail and to explore how substance use and other psychiatric features affect this relationship. Methods: Prospective cohort study, conducted at the 'Sant'Anna' jail in Modena (Italy) between February 2017 and September 2019. Socio-demographic, psychiatric features and records of previous SSHB were collected. Experience of migration-related trauma was assessed with the LiMEs (List of Migration Experiences) checklist. Participants were followed-up for the occurrence of further SSHB. Survival analysis was performed and Cox's Hazard Ratios (HR) were used as a measure of association of comparisons. Results: Amongst the 112 subjects (96% male, median age 33), the prevalence of any mental disorder was 26% and of substance abuse 59%. History of SSHB was present in 36% of the sample. Median follow-up time was 80 days. During follow-up, 11 events were observed (of which three were suicide attempts). Cumulative survival probability was 85%. Having experienced trauma related to war and violence was significantly associated with SSHB, HR: 7.05. No SSHB were recorded amongst subjects without substance abuse. Conclusions: Migrants in custody who experienced trauma in the post-migration period, attempt SSHB seven times more frequently than those without traumas at any time. War trauma and post-migration trauma due to exposure to violence seem to be more strongly associated with SSHB, also controlling for psychiatric diagnosis, ongoing psychopharmacological therapy and substance abuse. Further research and possible intervention programs should focus on addressing post-migration living-difficulties.